"Rycerze czarnego toru" - wizerunek żużlowca-rycerza utrwalony w języku i twórczości kibiców = "The knights of the black track" - the image of the knight speedway rider preserved in the language and speedway fans' works - Roszak, Maria (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The article presents the image of the speedway rider, identified with the medieval knight and preserved in the language and works of speedway fans. The language material was excerpted from the slogans, songs etc. of the black sport fans and their statements, published in fan song books and online forums. The linguistic resource was enriched with terminology and professional vocabulary.
Keywords: język środowiskowy; język kibiców żużlowych; kibice; żużel; stereotyp rycerza; jargon; language of speedway fans; supporters; speedway; stereotype of the knight